Assistance in developing the Baha Tourism Village, Bali - Dewa Putu Oka Prasiasa; Ida Bagus Gede Udiyana; Gusti Ayu Mahanavami; Ni Ketut Karwini (Universitas Muhammadiyah Magelang, 2023)
Assistance for the Baha Tourism Village, Mengwi District, Badung Regency aims to ensure that the tourism village can develop properly and provide socio-cultural and economic benefits for the local community. The methods used in this assistance are community education methods, training, science and technology substitution, and participatory decision making processes. Assistance to the Baha Tourism Village has resulted in increased public awareness of cleanliness along the tracking/cycling route, additional supporting infrastructure along the tracking/cycling route, the formation of an organizational structure for managing the tourism village, the availability of Baha Village tour packages, and digital promotion through the Godevi platform. The Baha Village tour package consists of tracking/cycling routes, historical tours of Japanese Caves, traditional culinary (lawar Nyawan), traditional games (metembing and mesorog-sorogan), traditional architecture of Pura Puseh Baha Village, folklore (Men Brayut and Pan Brayut), and jerimpen.